2020
DOI: 10.3390/ijerph17020418
|View full text |Cite
|
Sign up to set email alerts
|

Family Income Gradients in Adolescent Obesity, Overweight and Adiposity Persist in Extremely Deprived and Extremely Affluent Neighbourhoods but Not in Middle-Class Neighbourhoods: Evidence from the UK Millennium Cohort Study

Abstract: We investigated whether family income gradients in obesity, overweight, and adiposity persist at geographic-level deprivation quintiles using a nationally representative cohort of UK adolescents. Data from 11,714 eligible adolescents from the sixth sweep of the Millennium Cohort Study (14 years old) were analysed in this study. The International Obesity Task Force age- and sex-specific thresholds were used to define obesity and overweight. Self-reported family income was standardized using the Organisation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…This may explain the rather small additional relative risk (2%) of being a short sleeper for a 10-minute increase in digital media time; this is consistent with a recent findings using the same data that reported very small inverse association between bedtime use of digital media and sleep duration [30]. Several studies have investigated emerging hypothesis that short sleep duration in adolescence is associated with the higher risks of obesity and overweight [31][32][33][34][35]. Although these studies account for physical activity, none has investigated an interaction between physical activity and short sleep on the risk of obesity.…”
Section: Discussionsupporting
confidence: 85%
“…This may explain the rather small additional relative risk (2%) of being a short sleeper for a 10-minute increase in digital media time; this is consistent with a recent findings using the same data that reported very small inverse association between bedtime use of digital media and sleep duration [30]. Several studies have investigated emerging hypothesis that short sleep duration in adolescence is associated with the higher risks of obesity and overweight [31][32][33][34][35]. Although these studies account for physical activity, none has investigated an interaction between physical activity and short sleep on the risk of obesity.…”
Section: Discussionsupporting
confidence: 85%
“…1,2 Studies in the UK using area-level SEP in relation to body composition have reported mixed results. [12][13][14] Although area-level SEP has often been used as a proxy for individual circumstances, it is likely to also capture broader aspects, specifically social and economic aspects, of the environment in which people live. Conceptual models have highlighted how neighbourhood deprivation relates to obesity through the built and social environment.…”
Section: Introductionmentioning
confidence: 99%
“…Age was calculated as the elapsed time between the child’s date of birth and the date of the sixth sweep assessment; which was also used to infer season of measurement. Adolescents self-reported their ethnic group [24] and parents reported their incomes which were equivalised to indicate net disposable household income per week [25]. Birth weight and the child’s breast feeding history were also parent reported.…”
Section: Methodsmentioning
confidence: 99%